MotionSure: a cloud-based algorithm for detection of injected object in data in motion - Islam, Thouhedul; Olanrewaju, Rashidah Funke; Khalifa, Othman Omran (Institute of Electrical and Electronics Engineers Inc., 2017)
One of the problems in cloud computing data security is injected object during data movement from one state to another. Mostly, the Man In The Middle (MITM) attack happens in this stage by hijacking active session variables, manipulating files and objects. Although there are few algorithms for data protection in the Cloud, However, such algorithms are still prone to attack, especially in real-time data movement due to the mechanism employed. This paper proposes a secure autodetection of an injected object based on hash function labelling; a one-time security header for transferable files that protects an unauthorized injection. The labelling header allows two-way data binding; DOM based communication between local and cloud computing that triggers automated acknowledgement immediately after file modification. Two encryption functions in PHP has been used for detecting injected object; bcrypt methods in Laravel and MD5 that generate 32 random keys. Total 1600 different type of files were used for evaluation of the proposed algorithm, results show that 87% of injected objects were correctly detected